Exercise effects on serum levels of creatine kinase in ultra-distance triathletes in the course of a competition period Efeito do exercício nas concentrações séricas de creatina cinase em triatletas de ultradistância - Machado C.N.* (2010)
Triathlon is a popular sport with world wide participation. It combines three different endurance modalities - swimming, cycling and running - within a single event. There is a variety of distances on which triathlon events are made, the Ironman race being the longest. Many authors have already reported injury occurrence after intense exertion, either directly, through histological sarcomere alterations, or indirectly, over the quantification of specific muscle proteins concentration (injury biomarkers) in the plasma. Among these markers of muscle injury, Myoglobin and Creatine Kinase stand out. In fact, creatine kinase is the most used biochemical indicator of muscle injury occurrence. Within this context, it is justified the purpose of this study, that intends to verify exercise effects on serum levels of creatine kinase in ultra-distance triathletes in the course of a competition period. Serum levels of CK from 10 triathletes who competed in the Ironman Brazil event, 2007 were evaluated. Blood analyses were done at five distinct periods: 19 days before Ironman Brazil competition (CK1), 48 hours before it (CK2), immediately after it (CK3), five days after the competition (CK4) and 12 days after the event (CK5). The results showed significant increase on CK concentrations at periods 3 and 4, when compared to the other evaluated periods. These alterations evidence the influence of the Ironman competition exhaustive exercise over the CK concentrations, revealing the possibility of muscle injuries development during the event. This fact enhances the importance of biomarkers' monitoring, like CK, that allow coaches and athletes to adapt training loads to increase their benefits and to avoid overtraining, improving performance, health and quality of life.